Odpowiedzi

2010-03-12T19:06:46+01:00
A)
∫(1/√x - 3x)² dx
Obliczę najpierw
(1/√x - 3x)² = 1/x -6x/√x + 9 x² = 1/x - 6√x +9 x²
założenie : x > 0
mamy zatem
∫(1/√x - 3x)² dx = ∫[1/x -6√x + 9 x²] dx =
= ∫(1/x) dx - 6∫√x dx +9 ∫ x² dx =
= ln I x I - 6*2√x + 9*x³/3 + C = ln I x I - 12 √x + 3 x³ + C
b)
(x +2)²/ x =[x² +4x +4]/x = x + 4 + 4/x
założenie x ≠ 0
∫(x+2)²/x dx = ∫[x +4 + 4/x] dx = ∫x dx +∫4 dx + 4∫dx/x =
= 0,5 x² +4x + 4 *ln I x I + C
zatem całka oznaczona
₁∫² (x +2)²/x dx = [ 0,5 x² +4x + 4*ln I xI ]²₁ =
= 0,5*2² +4*2 + 4 * ln 2 - 0,5*1² - 4*1 - 4 *ln 1 =
= 2 + 8 + 4 ln 2 - 0,5 - 4 =
= 5,5 + 4 ln 2 , ( bo ln 1 = 0 )